Rationale, design, and baseline characteristics of the CLARIFY registry of outpatients with stable coronary artery disease. Issue 10 (31st May 2017) - Sorbets, Emmanuel; Greenlaw, Nicola; Ferrari, Roberto; Ford, Ian; Fox, Kim M.; Tardif, Jean‐Claude; Tendera, Michal; Steg, Philippe Gabriel; ,
Abstract : Background: Despite major advances in prevention and treatment, coronary artery disease (CAD) remains the leading cause of death worldwide. Whereas many sources of data are available on the epidemiology of acute coronary syndromes, fewer datasets reflect the contemporary management and outcomes of stable CAD patients. Hypothesis: A worldwide contemporary registry would improve our knowledge about stable CAD. The main objectives are to describe the demographics, clinical profile, contemporary management and outcomes of outpatients with stable CAD; to identify gaps between evidence and treatment; and to investigate long‐term prognostic determinants. Methods: CLARIFY (ProspeCtive observational LongitudinAl RegIstry oF patients with stable coronary arterY disease) is an ongoing international observational longitudinal registry. Stable CAD patients from 45 countries in Europe, Asia, America, Middle East, Australia and Africa were enrolled between November 2009 and June 2010. The inclusion criteria were previous myocardial infarction, evidence of coronary stenosis >50%, proven symptomatic myocardial ischemia or prior revascularization procedure. The main exclusion criteria were serious non‐cardiovascular disease, conditions interfering with life expectancy or severe other cardiovascular disease (including advanced heart failure). Follow‐up visits were planned annually for up to 5 years, interspersed with 6‐month telephone calls. Results: Of the 32, 703 patients enrolled, most (77.6%) were male, age (mean ± SD) was 64.2 ± 10.5 years, and 71.0% were receiving treatment for hypertension; mean ± SD resting heart rate was 68.2 ± 10.6 bpm. Patients were enrolled based on a history of myocardial infarction >3 months earlier (57.7%), having at least one stenosis >50% on coronary angiography (61.1%), proven symptomatic myocardial ischemia on non‐invasive testing (23.1%), or history of percutaneous coronary intervention or coronary artery bypass graft (69.8%). Baseline characteristics were similar across the four subgroups identified by the four inclusion criteria. Conclusion: CLARIFY will provide a useful resource for understanding the current epidemiology of stable CAD.